1970
DOI: 10.1136/bmj.3.5715.135
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Studies of the Modified Kiil Dialyser

Abstract: ummary: Bacterial proliferation in dialysis fluid during haemodialysis may be associated with rigors, hypotension, and bacteraemia. Investigations carried out in a period in which rigors were particularly common showed the source of bacteria to be parts of the gasket system of the Kiil dialyser, areas that are inaccessible to disinfectants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In this respect we would disagree with Fregerslev (7) who suggested all fluids including hemotrate be sterilized. Rather, we agree with Jones et al (10) and suggest that the levels of bacterial contamination be maintained at a low level, preferably less than 1,000/ml. Requirements for sterile source water or dialysate fluid would be most unrealistic since no manufacturer can currently meet that specification.…”
Section: Discussionsupporting
confidence: 92%
“…In this respect we would disagree with Fregerslev (7) who suggested all fluids including hemotrate be sterilized. Rather, we agree with Jones et al (10) and suggest that the levels of bacterial contamination be maintained at a low level, preferably less than 1,000/ml. Requirements for sterile source water or dialysate fluid would be most unrealistic since no manufacturer can currently meet that specification.…”
Section: Discussionsupporting
confidence: 92%
“…Further evidence against the role of live bacteria in producing dialysis reactions is shown by the lack of correlation with positive blood cultures. Jones et al (1970) suggested that dialysis reactions are produced by the entry into the blood of bacteria from the dialysate compartment and demonstrated the persistence of bacteria in Kiil boards exposed to 2% formaldehyde. The incidence of reactions in our patients did not correlate with the presence of bacteria in samples of priming saline taken from the blood compartment of the dialysers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of sterile, disposable dialysers clinical reactions caused by bacterial contamination of the dialysate are still in evidence. The frequency has been reported to be about 10% (14) and a good correlation has been found between the degree of contamination and the severity of the reactions (6,7, 9,10,12).…”
Section: Discussionmentioning
confidence: 97%